Enhancing Social-Emotional Learning in Elementary Schools: The 4Rs Strategy (Reading, Writing, Respect, and Resolution) - Rashika Ardafa Sahila; Unik Ambar Wati; Ika Damayanti; Edy Mawardi; A.S Almunawwarah (AL-ISHLAH: Jurnal Pendidikan, 2025)
In the context of Industry 4.0, students are increasingly exposed to complex emotional and social challenges that often carry over into the school environment. These evolving dynamics pose a significant challenge for educators, especially when students struggle to identify and manage their emotions. To address this, effective strategies in social emotional learning (SEL) are crucial. This study explores the application of the 4Rs model—Reading, Writing, Respecting, and Resolving—as a framework to enhance students’ empathy and emotional self-regulation at SD Muhammadiyah Suronatan, with a focus on identifying both its supporting and inhibiting factors. Using a qualitative case study approach, data were collected through classroom observations, interviews with teachers and students, and analysis of school documentation. This method provided an in-depth understanding of how the 4Rs model supports SEL development in an elementary school setting. The findings demonstrate that the 4Rs model has a meaningful impact on students' social and emotional growth. Reading activities helped students recognize and understand various emotions, while writing tasks encouraged them to express and reflect on their feelings. Respecting, in the form of appreciation activities, strengthened the emotional bond between teachers and students and promoted a more empathetic classroom environment. Finally, resolution activities provided structured opportunities for students to engage in decision-making and conflict resolution. In conclusion, the integration of the 4Rs model has proven effective in promoting empathy and emotional regulation among students. These findings offer valuable insights for other elementary schools seeking to implement SEL strategies that respond to the demands of Industry 4.0.